An Empirical Exploration of Factors Contributing to Malaysian Men Becoming Involved in a Feminine Career: A Case Study of Male Nurse and Pak Andam - Siti Salina Abdullah ,; Suhaili Arifin,; Fazliyaton Ramley,; Zakaria Mohamad,; Mohd Sani Ismail,; Khuzaimah Mustapa, (Asian Academy of Management Journal, 2024)
The gender socialisation process will form and affect the career choices of children when they grow up. As a result, certain careers are considered appropriate only for a certain gender. However, this scenario of gender dominated career is now loosened. Currently, there are men who work as nurses, secretaries, and bridal beauticians. This study examines the factors that influence Malay, Muslim Malaysian men to work in two careers generally dominated by women, which are nurse and “pak andam” (Malay bridal beautician and consultant). Using a case study qualitative approach, the author investigated the factors that influence male nurses (N = 14) and “pak andam” (N = 5) to work in occupations generally considered to be the main domain of women in Malaysia’s culture. Data from semi-structured interviews revealed that the reason why men become male nurses is mainly caused by external factors, which are family obedience, financial disadvantage, and  religious obligation. However, during their journey in becoming nurses, they developed their passion for nursing. In contrast, the males who become “pak andam” do so mainly because of personal factors, which is their interest in beauty and fashion. This paper will further discuss the participants’ experiences from the context of Malay Muslim culture.